2016
DOI: 10.1128/aem.03821-15
|View full text |Cite
|
Sign up to set email alerts
|

Global Genomic Epidemiology of Salmonella enterica Serovar Typhimurium DT104

Abstract: It has been 30 years since the initial emergence and subsequent rapid global spread of multidrug-resistant Salmonella enterica serovar Typhimurium DT104 (MDR DT104). Nonetheless, its origin and transmission route have never been revealed. We used whole-genome sequencing (WGS) and temporally structured sequence analysis within a Bayesian framework to reconstruct temporal and spatial phylogenetic trees and estimate the rates of mutation and divergence times of 315 S. Typhimurium DT104 isolates sampled from 1969 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
124
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 57 publications
16
124
0
1
Order By: Relevance
“…The clade shared high core genome similarity with a contextual DT104 genome from Scotland. From the identity of AMR genotype and phenotype and the estimated year of MRCA, we infer that the cluster 7 clade belonged to the global pandemic of MDR DT104, which spread across Europe, Asia and America from the 1970s [59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clade shared high core genome similarity with a contextual DT104 genome from Scotland. From the identity of AMR genotype and phenotype and the estimated year of MRCA, we infer that the cluster 7 clade belonged to the global pandemic of MDR DT104, which spread across Europe, Asia and America from the 1970s [59].…”
Section: Resultsmentioning
confidence: 99%
“…The MDR phenotype of cluster 7 was associated with two AMR gene patterns: A clade resistance to ampicillin, chloramphenicol, streptomycin, and tetracycline was related to the presence of aadA2, blaCARB-2, floR, tet(A) and tet(G); and the other clade was resistant to ampicillin, tetracycline and trimethoprim carried aph(3')-Ia, blaOXA-2, dfrA29, mphB, sul1, and tet(A). The former clade shared the similar AMR phenotype and genotype as the MDR DT104 that emerged globally in the 1990s, which also carried the aadA, floR, sul1 and tet(G) genes [59].…”
Section: Amr Genotype and Phenotypementioning
confidence: 96%
“…Cattle isolates were in both first order clades (11 in clade α 7 in clade β ), but in clade β they had a relatively limited distribution with five of the isolates from a subclade containing the DT204/49 complex of strains associated with a cattle associated epidemic in the 1970's 8 . Clade α contained strains from several previously described epidemics in livestock animal species, including in pigs (α12, U288) 17 , two clades associated with recent pandemic clonal groups associated with pigs, cattle and poultry (α17, monophasic Typhimurium ST34 and α15, DT104) [18][19][20] , and potentially epidemic clades not previously described in the literature, consisting of isolates from pigs, cattle and poultry (α8 6 and α11). Clade-β was characterised by many long internal branches, indicative of a relatively high level of sequence divergence, relative to those in Clade-α.…”
Section: Resultsmentioning
confidence: 99%
“…The emergence and dispersal of AMR Salmonella are particularly problematic, due to (i) the fact that nontyphoidal Salmonella represents one of the most common causes of foodborne disease cases and associated deaths worldwide (23) and (ii) reports on the emergence and dispersal of different multidrug-resistant Salmonella strains (e.g., Salmonella Typhimurium DT104) (24)(25)(26). Studies of the relationships between AMR determinants and MDR strains found in humans and animals are often confounded by the selection of the isolates included in a given study, in which human and animal isolates may be of different serotypes, geographical locations, or temporal intervals.…”
Section: Discussionmentioning
confidence: 99%